2007
DOI: 10.1097/blo.0b013e318059b8eb
|View full text |Cite
|
Sign up to set email alerts
|

Hemicortical Excision for Low-grade Selected Surface Sarcomas of Bone

Abstract: In malignant surface tumors, hemicortical excision in select cases may allow adequate margins with better function. We treated 10 of 22 malignant surface tumors with hemicortical excision and reconstruction from January 2000 to June 2003. There were eight conventional parosteal osteosarcomas, one high-grade surface osteosarcoma, and one surface chondrosarcoma. Six tumors occurred in the femur, two in the tibia and one each in the humerus and radius. Defects were reconstructed with allograft (five), fibula auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 12 publications
3
36
0
Order By: Relevance
“…With the navigation guidance, we could reproduce the planned resection without any help of landmark measurements or intraoperative fluoroscopy. Some authors have reported the use of multiplanar osteotomies or hemicortical resection to treat select patients with bone sarcoma [1,3,5]. Our results in Patients 1, 5, 6, and 8 also suggest multiplanar osteotomies or hemicortical resection are possible around bone tumors.…”
Section: Discussionsupporting
confidence: 63%
“…With the navigation guidance, we could reproduce the planned resection without any help of landmark measurements or intraoperative fluoroscopy. Some authors have reported the use of multiplanar osteotomies or hemicortical resection to treat select patients with bone sarcoma [1,3,5]. Our results in Patients 1, 5, 6, and 8 also suggest multiplanar osteotomies or hemicortical resection are possible around bone tumors.…”
Section: Discussionsupporting
confidence: 63%
“…One study of 237 patients with high-grade osteosarcomas reported only 11% of patients who had local recurrences were living at the most recent followup [25]. Given the high risk of local recurrence with a contaminated margin [2] and the resulting poor prognosis, many physicians are reluctant to perform a resection that achieves less than generously wide margins [1,2]. In contrast, some authors have reported no local recurrences and no nonunions, with a resection technique used for low-grade surface osteosarcomas that retains part of the cortical circumference [1,8,19].…”
Section: Introductionmentioning
confidence: 97%
“…For high grade sarcomas, a wide margin is considered adequate and will achieve successful control of the primary tumor approximately 95% of the time, whereas marginal or intralesional margins are associated with higher rate of local recurrence and poor outcomes 26 . For bone 3cm away from the extent on T1-MRI image is adequate [27][28][29][30][31][32] . The marrow is always sent from the cut end for frozen section evaluation for tumour.…”
Section: Surgical Resections and Reconstructionsmentioning
confidence: 99%
“…We reported our results in ten cases with complete incorporation of the graft in all the cases and no local recurrence. 28 Fig. 2.…”
Section: Hemicortical Defectsmentioning
confidence: 99%
See 1 more Smart Citation